Effect of heavy increase in training stress on the plasma leptin concentration in highly trained male rowers - Mäestu, J.; Jürimäe, J.; Jürimäe, T. (Hormone Research, 2003)
To characterize the effects of a heavy increase in training stress followed by a reduced stress on fasting plasma leptin levels in highly trained male rowers. Methods: 12 rowers underwent a 3-week period of maximally increased training stress followed by a 2-week tapering period. Results: A mean 22% increase in training stress caused a significant decrease (by 8%) in the leptin concentrations. A further increase in training stress by 25% significantly reduced leptin further by 35%. A 1st tapering week, during which the training stress was rapidly reduced by approximately 50%, significantly increased the plasma leptin concentrations by 29%. Plasma leptin was significantly increased further (by 4%) during the 2nd tapering week. Conclusion: Leptin is sensitive to pronounced changes in training stress in highly trained male rowers.